ANALISIS KADAR KUERSETIN PADA EKSTRAK ETANOL DAUN MIANA (Plectranthus scutellarioides (L.) R.Br.) SECARA HPLC (High Performance Liquid Chromatography) - Sukmawati Sukmawati; Harti Widiastuti; Miftahuljanna Miftahuljanna (Fakultas Farmasi UMI, 2019)
One of the medicinal plants that people often use as a medicine is the Miana leaves (Plectranthus scutellarioides (L.) R.Br.). The Miana leaves are empirically used to treat coughs, heart disease, worm medicines, antimicrobials, antioxidants, antiseptics, bronchitis, hemorrhoids, tuberculosis, and other pharmacological activities. The miana leaves contain secondary metabolite compounds of flavonoids, steroids, tannins, and saponins. One of the most critical flavonoids is quercetin. This study aimed to determine the quercetin content of ethanol extract of miana leaves by HPLC (High Performance Liquid Cromatography). The extraction method by maceration using 96% ethanol. Determination of quercetin content in miana leaf ethanol extract by HPLC with C18 column, maximum wavelength of 369.11 nm with mobile phase methanol : aquabides (59:41) flow rate of 1 mL/minute. The results showed retention time for quercetin as a comparison of 4,183 minutes, a sample of 4.563 minutes, and an additional sample of 4,363 minutes. The average content of quercetin in miana leaf ethanol extract was 3.122 mg/g or 0,312%.